2003
DOI: 10.3171/jns.2003.98.1.0082
|View full text |Cite
|
Sign up to set email alerts
|

The natural history of hemangioblastomas of the central nervous system in patients with von Hippel—Lindau disease

Abstract: In this study the authors define the natural history of CNS hemangioblastomas associated with VHL disease. Not only were cysts commonly associated with cerebellar, brainstem, and spinal hemangioblastomas, the pace of enlargement was much faster for cysts than for hemangioblastomas. By the time symptoms appeared, the majority of mass effect-producing symptoms derived from the cyst, rather than from the tumor causing the cyst. These tumors often have multiple periods of tumor growth separated by periods of arres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
307
1
15

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 415 publications
(339 citation statements)
references
References 43 publications
16
307
1
15
Order By: Relevance
“…11,12 VHL disease is suggested to account for approximately a third of patients with a CNS haemangioblastoma, 450% of patients with a retinal angioma, 1% of patients with RCC, 50% of patients with apparently isolated familial phaeochromocytoma and 11% of patients with an apparently sporadic phaeochromocytoma 5,8,13 (and unpub- Haemangioblastomas with an associated cyst tend to become symptomatic sooner. 16 Microscopically, haemangioblastomas consist of large polygonal stromal cells enmeshed in a capillary network and stromal cells arise from mesoderm-derived embryologically arrested haemangioblasts. 17 Although CNS haemangioblastomas tend to enlarge over time, they are benign tumours and the growth rate is variable so that some tumours may be static for a number of years and hence removal of asymptomatic lesions is not usually indicated.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 VHL disease is suggested to account for approximately a third of patients with a CNS haemangioblastoma, 450% of patients with a retinal angioma, 1% of patients with RCC, 50% of patients with apparently isolated familial phaeochromocytoma and 11% of patients with an apparently sporadic phaeochromocytoma 5,8,13 (and unpub- Haemangioblastomas with an associated cyst tend to become symptomatic sooner. 16 Microscopically, haemangioblastomas consist of large polygonal stromal cells enmeshed in a capillary network and stromal cells arise from mesoderm-derived embryologically arrested haemangioblasts. 17 Although CNS haemangioblastomas tend to enlarge over time, they are benign tumours and the growth rate is variable so that some tumours may be static for a number of years and hence removal of asymptomatic lesions is not usually indicated.…”
Section: Introductionmentioning
confidence: 99%
“…These lesions are rarely malignant, but enlargement or bleeding within the CNS can result in neurological damage and death [Pavesi et al, 2008]. Studies have shown 44-72% of VHL patients acquire cerebellar hemangioblastomas and 13-44% develop spinal hemangioblastomas [Filling-Katz et al, 1991;Lamiell et al, 1989;Maher et al, 1990b;Wanebo et al, 2003]. VHL-associated cerebellar hemangioblastomas are diagnosed at a mean age of 29-33 years, almost 20 years earlier than sporadic cerebellar hemangioblastomas [Hes et al, 2000a[Hes et al, , 2000bWanebo et al, 2003].…”
Section: Introductionmentioning
confidence: 99%
“…VHL-associated cerebellar hemangioblastomas are diagnosed at a mean age of 29-33 years, almost 20 years earlier than sporadic cerebellar hemangioblastomas [Hes et al, 2000a[Hes et al, , 2000bWanebo et al, 2003]. Wanebo et al [2003] showed most CNS hemangioblastomas were associated with cysts that were often larger than the hemangioblastomas. Tumor growth commonly cycled between growth and quiescent phases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients need to be screened for CNS haemangioblastoma, retinal angioma, clear cell renal cell carcinoma, pancreatic neuroendocrine tumours (which are seen in around 10%) and middle ear tumours regularly. Haemangioblastomas are the most common lesions associated with VHL disease, affecting 60 to 84%, typically occurring in the cerebellum or spinal cord (22). The incidence of development retinal (cofactor of flavin adenine dinucleotide), has now been recognised.…”
Section: Familial Catecholamine-hypersecreting Tumours In Succinate Dmentioning
confidence: 99%